Improvement of cattle oocyte retrieval techniques and hormonal influence on in vitro embryonic development - Lekola, Khomotso Podile Molvia (University of Limpopo, 2015)
The objectives of this study were: 1) To determine the effect of oocyte retrieval techniques (slicing and aspiration) on the quality and quantity of cattle oocytes, 2) To evaluate the effect of different concentrations of hormones on the maturational rate of cattle oocytes selected by brilliant cresyl blue staining, 3) To evaluate fertilization rate and cleavage/embryonic development of oocytes with or without cumulus cells, and 4) To compare the effect of fresh and frozen thawed semen on the fertilization rate of cattle oocytes. In Experiment 1: oocytes were recovered from abattoir derived ovaries using slicing and aspiration. The recovered oocytes were exposed for 90 minutes to 26μM of brilliant cresyl blue (BCB) stain and classified according to the colour of their cytoplasm: BCB+ (oocytes with blue cytoplasm) and BCB- (unstained oocytes). There was no difference (P>0.05) in the quality of oocytes recovered using slicing (60.7 %) or aspiration (53.7 %) techniques. In experiment 2: The BCB selected and the non-selected immature oocytes were randomly allocated into medium 199 + 10 % fetal bovine serum (FBS) maturation media. The media was supplemented with three different concentrations of hormones as treatments (T). The T1 (0.5 μg/ml of follicle stimulating hormone (FSH), 5mg/ml of luteinizing hormone (LH) and 2 μg/ml of estradiol (E2) as the control group. Then, T2 (1 μg/ml of FSH, 6 mg/ml of LH and 2.5 μg/ml of E2) and T3 (1.5 μg/ml of FSH, 7 mg/ml of LH and 4.5 μg/ml of E2). Maturation rate of oocytes was determined by the protrusion of the first polar bodies 24 hours following in vitro maturation. Treatment 2 yielded higher (P<0.05) maturation rate for both BCB+ (65.6 %) and without BCB (60.3 %) oocytes with T1 giving lower (P<0.05) maturation rate for BCB+ (22 %) and without BCB (16 %) oocytes. However, BCB- oocytes had lower (P<0.05) polar body extrusion (3.03 %, 8.1 % and 2.2 %) for T1, T2 and T3, respectively. In Experiment 3: one group of the presumptive zygotes was denuded of cumulus cells and the other group was cultured with cumulus cells. The presumptive zygotes were in vitro cultured in SOF-BSA and changed to SOF-FBS after 48 hours. High fertilization/cleavage rate was observed in oocytes cultured with cumulus cells (29.0 %) compared to the denuded oocytes (20.0 %) for 2-4 cells stage. Day 7 blastocysts were more (P<0.05) on oocytes cultured with cumulus cells (32 %) compared to denuded oocytes (13 %). In experiment 4: The matured oocytes were fertilized using fresh and frozen thawed semen. The oocytes fertilized with frozen thawed semen obtained a better number of 2-4 cell cleavage (23 %) when compared to fresh semen (19 %). Oocytes that were fertilized with frozen thawed semen also obtained higher morula (13 %) and blastocyst (8 %) compared to fresh semen with morula (3.4 %) and blastocyst (2 %). In conclusion, immature oocytes that were exposed to BCB+ and cultured in M199 supplemented with 10 % FBS, 0.5 μg/ml of FSH, 5 mg/ml of LH and 2 μg/ml of E2 had a higher (P<0.05) number of matured oocytes (extrusion of first polar body) compared to those that were not exposed to BCB (no BCB). Oocytes that were cultured with cumulus cells yielded a higher (P<0.05) number of cleaved embryos compared to the denuded oocytes. Slicing yielded a higher (P<0.05) number of oocytes, however the quality of oocytes recovered was similar compared to those recovered by the aspiration technique (P>0.05). Oocytes fertilized with frozen thawed semen yielded higher (P<0.05) number of 2-4 cell, morula and blastocyst when compared with oocytes that were fertilized using fresh semen. Keywords: ovaries, oocytes, slicing, aspiration, COCs, BCB, polar body and cattle
Thesis (M. Sc. (Animal Production)) -- University of Limpopo, 2015
Keywords: Ovaries; Oocytes; COCS; Polar body and cattle; Ovarian atresia; Cattle -- Anatomy.